Skull Base Surgery - Borghei-Razavi, Hamid; Mandel, Mauricio; Suero Molina, Eric (IntechOpen, 2022)
This comprehensive multidisciplinary book discusses skull base surgery. Due to complex anatomy and important functional structures, there are specific conditions for surgical procedures at the skull base. Chapters address the specifics, intricacies, and applications of different surgical techniques and approaches for each type of skull base tumor pathology. It is designed for neurosurgeons who are interested in learning more about skull base surgery and implementing its different methods and techniques into their practices.